2012
DOI: 10.1080/13606719.2011.638205
|View full text |Cite
|
Sign up to set email alerts
|

Community sports projects and effective community empowerment: a case study in Rochdale

Abstract: How can community empowerment be most effectively achieved through the use of sport? In a case study of a bespoke voluntary sector project, an action research approach revealed insights into effective community empowerment. Although focused on a comparatively small project within a provincial UK town, the issues addressed and lessons learned can be generalised and transferred much more universally to community-based sports delivery. Detached from mainstream providers, and more agile and responsive to local nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 21 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Elsewhere, Partington and Totten have described how sport can become critical praxis and utilized as a form of emancipatory action research to challenge dominant institutions. 67 For core fans it was important that their politics was not just limited to ideas but linked to action too. Participants distinguished between being politically minded and actually being politically active pointing out that the degree of activism is not consistent; I see a difference between the inner circle supporters (the die-hard supporters) and the rest of the supporters.…”
Section: Political Imagination and Praxismentioning
confidence: 99%
See 1 more Smart Citation
“…Elsewhere, Partington and Totten have described how sport can become critical praxis and utilized as a form of emancipatory action research to challenge dominant institutions. 67 For core fans it was important that their politics was not just limited to ideas but linked to action too. Participants distinguished between being politically minded and actually being politically active pointing out that the degree of activism is not consistent; I see a difference between the inner circle supporters (the die-hard supporters) and the rest of the supporters.…”
Section: Political Imagination and Praxismentioning
confidence: 99%
“…Sport clearly has the potential to act as part of a wider social movement, engage in resistance and enable challenges to dominant structures of power (Partington and Totten 2012, Budd 2001). 8 Maguire describes power as an 'essential feature of the networks of interdependency' and further that 'forms of interdependency are contoured by power relations'. 9 While power is an omnipresent feature of all social life, including sport, Sugden and Tomlinson establish through Giddens that power is not a zero sum game but the 'dialectic of control'.…”
Section: Introductionmentioning
confidence: 99%
“…Building on the literature presented above, conceptualisations pertinent to sense of community are important to acknowledge here – since these ideas will assist the framing and interpretations in the subsequent analysis and support the development of social capital. Social capital and discussions of community refer to the binding of people in a particular location to establish a sense of empowerment through enterprise and entrepreneurship activity (Altinay et al., 2016; Partington and Totten, 2012; Waitt and Gibson, 2009; Zhao et al., 2011).…”
Section: Research Frameworkmentioning
confidence: 99%
“…Considering the various positive external effects of sports for all such as social inclusion and the creation of social capital, some research has suggested that non-profit sport clubs in particular are liable to create those effects (Coalter 2007, Skinner et al 2008, Partington and Totten 2012. Other research dealing with the impact of sport on social integration (e.g.…”
Section: Introductionmentioning
confidence: 97%